Catalytic pyrolysis of washed palm pressed fiber using cobalt oxide coated onto silica catalyst - Ronny Ling Leh Lung (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Palm pressed fiber (PPF) is one of the oil palm wastes of the rapidly expanding palm oil industry. The research describe in this paper is to investigate the behavior of catalytic pyrolysis of washed PPF using cobalt oxide catalyst. The catalyst was prepared by using wet-impregnation technique in which cobalt (II) oxide was coated onto silica oxide (Co/SiO2) according to molar ratio 1:10. The pyrolysis experiments were carried out in a fixed bed tubular reactor under inert atmosphere at temperature range from 450 - 550 o C, holding time of 30 - 90s and category of catalytic and non - catalytic. It was found that the pyrolysis of washed PPF in the presence of catalyst can derived a higher yield of bio-oil than non-catalytic reaction. The highest percentage of bio-oil obtained for catalytic reaction was 49.5 %, whereas the highest yield of bio-oil for uncatalytic reaction was 47.5 %. This study uses Design Expert software to screen out the important parameters that play significant role in the production of bio-oil. From the analysis of variance (ANOVA), factors that imposed the most significant effect on the yield of bio-oil were pyrolysis temperature (A), category (C) and interaction between holding time and category (BC). The liquid products were analyzed by using fourier transform infrared (FTIR) spectroscopy to identify the functional groups of bio-oil. From the FTIR analysis, the major compounds found in the bio-oil were alkanes, alkenes, aldehydes, ketones, phenols and alcohols. The physical properties of the synthesized catalyst were analyzed using scanning electron microscope (SEM) and x-ray diffraction (XRD) method. SEM analysis revealed the indefinite shape of synthesized catalyst. For XRD analysis, the studied catalyst was a crystalline structure with lots of impurities.